THE STUDY OF LEXEMES REPRESENTING THE MOVEMENT OF HUMAN BODY IN UZBEK AND ENGLISH - Avezova Nigora Safarovna (Galaxy International Interdisciplinary Research Journal, 2023)
In the world of linguistics, are recognized worldwide as a separate somatisms lexico-semantic group, the structural-semantic and communicative-pragmatic aspects, mechanisms of implementation of speech, translotological their properties are covered in a wide range of studies. On this basi, the definition of national-cultural, gender, stylistic-in function, cognitive-pragmatic, the Uzbek language and connotative features of somatisms in to the server denotativ further strengthen the scientific foundation and practical comparative linguistics, translation studies, translation from one language to another allows us to identify the principles of somatisms, language and speech, folic have language and literary language.